Viability of Newly Developed Processes for Catalytic Conversion of Bio-Glycerin into various “Green Chemicals”: Are there any Development Opportunities for Serbia in this Field? - Popovíć, Zoran M; Souček, Ivan; Ocić, Ozren J; Marinković, Dalibor M (Journal of Applied Engineering Science, 2016)
Crude bio-glycerin is a by-product in the production of biodiesel fuels. An economically efficient valorization of crude bio-glycerin usually significantly defines the profitability of the biodiesel plant. A strong technological development in recent years has provided an additional option for economically viable use of glycerin through conversion of a crude bio-glycerin: in first step into a technical glycerin, and then further into various "green chemicals". Many of those newly-developed technologies are already in use on an industrial scale. This trend had caused a growth in demand of bio-glycerin, which gradually has led to a rise of bio-glycerin's market value and contributed to an overall growth in profitability of biodiesel industry. This paper has the aim to assess: (1) global availability of the emerging technologies intended for valorization of bio-glycerin via production of commercially attractive "green chemicals", (2) local and regional availability of bio-glycerin for an economically justifiable production of "green chemicals", and (3) local and regional potential for marketing of the most viable "green chemicals". All market assessments and expected challenges that are stated in this paper took into account a reality that development of the biodiesel industry is still largely influenced by government subsidies and mandates, and also by a price of crude oil.